2009
DOI: 10.1530/rep-08-0471
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive potential of porcine and feline zona pellucida A, B and C subunits in domestic cats

Abstract: Feral cat populations are a major problem in many urban regions throughout the world, threatening biodiversity. Immunocontraception is considered as an alternative and a more humane means to control overpopulation of pest animals than current methods including trapping, poisoning and shooting. In this study, we evaluate porcine zona pellucida (ZP) polypeptide (55 kDa) and feline ZP A, B and C subunits expressed by plasmid vectors as candidate vaccines against fertility in the female domestic cat. Cats were inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
0
18
0
2
Order By: Relevance
“…These differences are partly responsible for the variable results obtained when using a particular ZP vaccine on different species and have been exploited to make ZP-based vaccines more specific (Kitchener et al 2009;Levy 2011). Porcine ZP (PZP) immunocontraceptive vaccines, derived from ZP isolated from pig ovaries, have been effective in many ungulate species, monkeys, seals, bears and marsupials, but not in rodents, cats, dogs and wild pigs (Eade et al 2009;Kitchener et al 2009;Kirkpatrick et al 2009Kirkpatrick et al , 2011 McLaughlin and Aitken 2011; Table 1). However, recently formulated recombinant PZP3 and PZP4 vaccines, delivered in three injectable doses, caused infertility in up to 89% mice, depending on the formulation type (Gupta et al 2013).…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 99%
“…These differences are partly responsible for the variable results obtained when using a particular ZP vaccine on different species and have been exploited to make ZP-based vaccines more specific (Kitchener et al 2009;Levy 2011). Porcine ZP (PZP) immunocontraceptive vaccines, derived from ZP isolated from pig ovaries, have been effective in many ungulate species, monkeys, seals, bears and marsupials, but not in rodents, cats, dogs and wild pigs (Eade et al 2009;Kitchener et al 2009;Kirkpatrick et al 2009Kirkpatrick et al , 2011 McLaughlin and Aitken 2011; Table 1). However, recently formulated recombinant PZP3 and PZP4 vaccines, delivered in three injectable doses, caused infertility in up to 89% mice, depending on the formulation type (Gupta et al 2013).…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 99%
“…Vaccination with native porcine ZP has been used in different species successfully [49][50][51]. However, in cats the effect of immunization with porcine ZP is not clear, and contradictory results have been obtained [52][53][54][55][56]. Moreover, the different ZP composition could explain the lack of efficiency of some heterospecific antigens when they are used as anticonception vaccines in cat [53,57].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the use of two proteins in the cat is more efficient than the use of only one ZP protein [56]. Probably, the development of a contraceptive vaccine including the ZP1 as an antigen would be beneficial because the antibodies produced against ZP1 reduce sperm binding to the ZP [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is based on the induction of antibodies against epididymal or testicular proteins so that they do not associate with the sperm surface or mask them to prevent interaction with other proteins for maturation. Examples include: antisperm antibodies (Vazquez-Levin (Luo et al, 2012), eppin (O'Rand et al, 2006), Bin1b (Li et al, 2001), FA-1 (Naz and Zhu, 1998), LDH-C4 (O'Hern et al, 1997), P10G (O'Rand et al, 1993, A9D (Lea et al, 1998), SP56 (Hardy and Mobbs, 1999), 80 kDa HSA (Khobarekar et al, 2008), YLP12 (Naz and Chauhan, 2002), zona pellucida proteins (Eade et al, 2009), and Izumo (Naz, 2008;Wang et al, 2009). We previously demonstrated that the rat PATE proteins are localized on the sperm surface and are predicted to play a role in sperm function (Rajesh and Yenugu, 2012).…”
Section: Discussionmentioning
confidence: 99%